jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2

jeśli a=0

-dla m=-1 równanie ma postać 1=0

-dla m=1 równanie ma postać 2x+1=0, czyli x=1/2